Implementasi Program Brus dalam Pencegahan Pernikahan Dini: Analisis Maqāṣid Al-Syarī’ah dan Hukum Positif: Implementation of the Brus Program in Preventing Early Marriage: Analysis of Maqāṣid Al-Syarī’ah and Positive Law - Miftahul Munir; Wasman (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2026)
This study analyzes the implementation and effectiveness of the Harmonious School-Age Youth Guidance Program (BRUSH) in preventing early marriage at the Religious Affairs Office (KUA) of Bodeh District, Pemalang Regency, through the perspectives of Maqashid Syariah and Indonesian positive law. The research aims to assess how BRUSH functions as an educational and preventive tool in fostering legal, moral, and spiritual awareness among adolescents. Employing a qualitative case study approach, data were collected through interviews, observations, and document analysis. The findings indicate that BRUSH is implemented through collaboration among KUA officers, schools, and religious counselors, using interactive methods such as group education, thematic guidance, discussions, and pre-marital simulations focusing on participants’ psychological, legal, and religious readiness. The program effectively reduces early marriage interest and enhances youth literacy on marriage values and reproductive health. Normatively, BRUSH reflects the five objectives of Maqashid Syariah (ḥifẓ ad-dīn, an-nafs, al-‘aql, an-nasl, al-māl) and aligns with Law No. 16 of 2019 on Marriage and Law No. 35 of 2014 on Child Protection. This study contributes to integrating Islamic and national legal frameworks in youth protection policies and strengthens pre-marital education based on Maqashid Syariah at the local level.